Neuroendocrinology and Behavior - Sumiyoshi, Tomiki (IntechOpen, 2012)
Understanding of the neuroendocrine system provides an insight into a wide range of bodily and mental processes. Neuroendocrinology and Behavior brings its readers a concise guide to up-to-date knowledge on the function of the endocrine glands and organs in association with neurotransmitters, neuropeptides, and behavioral manifestations. Various forms of stress response, e.g. anxiety and cognitive changes, have been intrinsic to both ourselves and other species. Specifically, these mechanisms involve complex interplays among physical, emotional, and behavioral processes in humans. This volume provides information on peptide hormones, i.e. oxytocin and vasopressin, and how studies of these neuropeptides enrich our understanding of social and other behaviors. These neuromodulators also affect sexual behavior and water balance in the body, an issue also addressed in this Book.